ART AND PROPAGANDA IN AN AGE OF WAR: THE ROLE OF POSTERS - Chambers, R. (Scientia Militaria - South African Journal of Military Studies, 2012)
Posters in this country have become one of the many means of communicating ideas; the message can be manipulative and they thus become a means of persuasion. They (can) reflect the mood of the times, the styles of their creators, they can be used to sell ideas and commodities and, (in the case of political posters), be used as a vehicle for the ideas of politicians and propagandists. Because they serve the (political) purpose of the moment, posters, like most other propaganda materials - pamphlets, banners, radio and TV broadcasts, leaflets, films, etc - are ephemeral and disposable.